Preparation of Novel Metal-Insulin Quantum Clusters for Bio-Imaging Applications. - Sharma, Shreya (My University, 2018)
This work focuses entirely on a simple and ascendable method for the synthesis of highly fluorescent Au, Cu, Zn, quantum-clusters (QCs) based on colloid synthesis via NaOH mediated synthesis. Exploiting noble metal like Au, and transition metals like Cu, Zn, as model metals. A facile methodology (total synthesis time < 2.5 h) complete with incubation at 37◦C at 240 rpm has been developed to process initially polydisperse, non-fluorescent, and unstable AuQCs, ZnQCs, CuQCs into monodisperse, highly fluorescent, and extremely stable AuQCs, CuQCs, ZnQCs in the same phase (aqueous) and Insulin as protein. The synthetic procedure was successfully stretched to assemble highly fluorescent protected by AuQCs, CuQCs, ZnQCs protected by Insulin, a small peptide hormone consisting of amino acids with functional groups like carboxyl, hydroxyl, and amine etc. The methodology adopted in this study should largely contribute to the practical applications of this new class of fluorescence clusters. In view of the protein protection, coupled with direct synthesis and easy functionalization, this hybrid QCprotein system is expected to have numerous optical and bioimaging applications in the future.
Master of Science- Biochemistry
Keywords: Insulin; Quantum Cluster; Bioimaging; Diabetes; Metallo Proteins